2019
DOI: 10.1002/hlca.201900076
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Synthesis and Transformations of Cationic CpRu(II)(naphthalene) and CpRu(II)(naphthoquinone) Complexes

Abstract: Details of the direct synthesis of cationic Ru(II)(η5‐Cp)(η6‐arene) complexes from ruthenocene using microwave heating are reported. Developed for the important catalyst precursor [Ru(II)(η5‐Cp)(η6‐1‐4,4a,8a‐naphthalene)][PF6] reaction time could be shortened from three days to 15 min. The method was extended to [Ru(II)(η6‐benzene)(η5‐Cp)][PF6], [Ru(II)(η5‐Cp)(η6‐toluene)][PF6], [Ru(II)(η5‐Cp)(η6‐mesitylene)][PF6], [Ru(II)(η5‐Cp)(η6‐hexamethylbenzene)][PF6], [Ru(II)(η5Cp)(η6‐indane)][PF6], [Ru(II)(η5‐Cp)(η6‐2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…However and unfortunately, previous attempts to perform anion metathesis of chloride to BAr F − by a direct exchange of [CpRu(η 6 ‐naphthalene)][Cl] with NaBAr F , were not met with success [57] . This problem could be circumvented in our hands starting from the [CpRu(η 6 ‐naphthalene)][PF 6 ] salt instead which was prepared following microwave assisted protocols [57,58] . In practice, a simple mixing for 30 min of NaBAr F and [1][PF 6 ] in a homogenous dichloromethane/acetone solution (1.2 : 1) provided, after crystallization from dichloromethane and hexane at 4 °C, the desired [CpRu(η 6 ‐naphthalene)][BAr F ] complex namely [1][BAr F ] in good yield (72 %, Scheme 2).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However and unfortunately, previous attempts to perform anion metathesis of chloride to BAr F − by a direct exchange of [CpRu(η 6 ‐naphthalene)][Cl] with NaBAr F , were not met with success [57] . This problem could be circumvented in our hands starting from the [CpRu(η 6 ‐naphthalene)][PF 6 ] salt instead which was prepared following microwave assisted protocols [57,58] . In practice, a simple mixing for 30 min of NaBAr F and [1][PF 6 ] in a homogenous dichloromethane/acetone solution (1.2 : 1) provided, after crystallization from dichloromethane and hexane at 4 °C, the desired [CpRu(η 6 ‐naphthalene)][BAr F ] complex namely [1][BAr F ] in good yield (72 %, Scheme 2).…”
Section: Resultsmentioning
confidence: 95%
“…[57] This problem could be circumvented in our hands starting from the [CpRu(η 6 -naphthalene)][PF 6 ] salt instead which was prepared following microwave assisted protocols. [57,58] In practice, a simple mixing for 30 netic profiles for carbene CÀ H insertions into THF or stereoselective epoxide openings, with a slight advantage for the BAr F derivative in the THF series. However, OTf and BF 4 complexes present quite lower reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…First, the nature of the metal catalyst was investigated, 2 switching from copper to dirhodium and cyclopentadienyl ruthenium complexes ( entries 3 and 4 ) while decreasing the temperature to 60 °C with these more reactive decomposition catalysts. Using Rh 2 (OAc) 4 (1 mol‐%), [45] a yield of 37 % was obtained, while decomposition with [CpRu(MeCN)] 3 PF 6 (2.5 mol‐%) [46,47] led to a drastic improvement and a corresponding yield of 80 %. Selecting the [CpRu] complex for further experiments, the influence of the negative counterion was investigated, switching from PF 6 − to the large, lipophilic and less coordinating BAr F − anion [42] .…”
Section: Resultsmentioning
confidence: 99%
“…Actually, when we used an excess amount of NQ (10 equiv) and PhCl as the solvent (bp = 131 °C), the yield of 3a improved to 77% (entry 5). The yield was further improved to 84% under a highly diluted concentration (entry 6, 0.025 M) …”
mentioning
confidence: 99%
“…These results might be attributed to the fact that the desired C–H bond activation pathway hardly proceeded. Regarding S1n ’s reactivity, there is a similar report on the o -tolyl group in the NHC . They investigated, by computational research, which activation, C–C or C–H bond, is thermodynamically preferred as the reaction product and concluded that the formation of the C–C bond activated complex was preferred.…”
mentioning
confidence: 99%